2017
DOI: 10.1111/pan.13298
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study comparing perioperative anxiety and posthospital behavior in children with autism spectrum disorder vs typically developing children undergoing outpatient surgery

Abstract: Findings revealed ratings of anxiety in youth with and without autism spectrum disorder facing surgery varied by reporter and setting, highlighting the importance of using multiple reporters in research of youth with autism spectrum disorder in the perioperative period. Furthermore, while results showed group differences in premedication patterns and induction compliance, groups did not differ in level of negative behavior change after surgery. Future research can examine how individual differences in youth wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Conversely, in a study on morbidity after tonsillectomy, children with ASD were less likely to experience complications [33]. However, anesthetic procedures have been shown to differ between children with ASD and those without [34], possibly impacting postoperative recovery. Communicative difficulties, and difficulties adhering to medical ordinations could plausibly increase the risk for complications in this group.…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, in a study on morbidity after tonsillectomy, children with ASD were less likely to experience complications [33]. However, anesthetic procedures have been shown to differ between children with ASD and those without [34], possibly impacting postoperative recovery. Communicative difficulties, and difficulties adhering to medical ordinations could plausibly increase the risk for complications in this group.…”
Section: Discussionmentioning
confidence: 96%
“…Anxiety and disruptive behaviour requiring sedation for children with ASD are common in the preoperative period, reported sedation rates in studies ranged from 76% -87.5% [17,18,19]. In our hospital, sedation is administered to the patient in the OT waiting area if deemed necessary by the attending anaesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…The research assistant reported increased anxiety and reduced compliance during induction of anesthesia in the autism spectrum group. However, when considering parental evaluation, anxiety was not greater and postoperative negative behavioral changes were similar in the two groups . While the study was limited by its small size and the fact that the anxiety assessment tools used are not validated in children with ASD, it remains valuable as a controlled study in adding to an objective body of evidence that is, for the most part, anecdotal and almost intuitive in nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, when considering parental evaluation, anxiety was not greater and postoperative negative behavioral changes were similar in the two groups. 5 While the study was limited by its small size and the fact that the anxiety assessment tools used are not validated in children with ASD, it remains valuable as a controlled study in adding to an objective body of evidence that is, for the most part, anecdotal and almost intuitive in nature. The provision of a calm quiet environment, allowance of comfort objects, minimized waiting times, and presence of the most appropriate caregiver (this may be a professional carer, parent, or both) are factors which can help in attenuating the anxiety that can occur in what is undoubtedly an intimidating environment.…”
Section: Introductionmentioning
confidence: 99%